Pathological Aspects of a Subclinical Marek's Disease Case in Free-Range Chickens - DLC Abreu (Brazilian Journal of Poultry Science, 2016)
Abstract The present report aims at describing the occurrence of Marek's Disease (MD) in a free range poultry farm based on macroscopic and microscopic lesions. For this purpose, seven free-range chickens were evaluated by gross and microscopic examination. Tumor lesions were observed in the liver and ovary, in addition of enlarged kidney and spleen, skin thickening and whitish lesions in streak form in the breast muscle. Fragments of the affected organs were collected and placed in 10% formalin for processing by the usual histopathology techniques, and stained with hematoxylin-eosin. Under microscopic evaluation, we observed pleomorphic populations of neoplastic lymphoreticular cells with pyknotic nuclei in the same organs, all compatible with MD. The macroscopic and microscopic lesions presented in this study were consistent with MD, meaning that the MD virus is present in the rearing environment of the studied chicken farm.